ELECTROCHEMICAL STUDIES OF THE OXIDATION OF PERSISTENT ORGANIC POLLUTANT 4-CHLOROPHENOL - Gilles, V.; Soares, T. F.; Andrade, A. R. De; Ribeiro, J. (Revista Brasileira de Engenharia de Biossistemas, 2014)
This paper aimed to prepare and characterize type electrodes dimensionally stable anodes, DSA® for degradation of organic compounds. The electrodes were prepared by thermal decomposition of polymeric precursor at 450° C with the following nominal compositions: Ti/Pt(30%) RuO2(10%)SnO2(60%), Ti/Pt(30%)RuO2(30%)SnO2(40%), and Ti/Pt(30%)RuO2(35%)SnO2(35%). The analysis by X-ray diffraction showed the presence of Pt on the metallic form with a face-centered cubic structure. Oxides of ruthenium and tin showed tetragonal structure and solid solutions formation at concentrations of ≥ 30% RuO2. The micrographs showed mud-cracked morphology for the electrodes with a high % atom of ruthenium. The analyzes carried out by cyclic voltammetry in an acid medium in the presence of 4-chlorophenol, 4-CF, showed the appearance of an anodic peak near 1.0 V vs. Ag/AgCl (KCl, 3.0 mol/L) being proportional to 4-CF concentration. Electrolysis test showed that the electrodes Ti/Pt(30%)RuO2(30%)SnO2(40%), and Ti/Pt(30%)RuO2(35%)SnO2(35%) are considerably more efficient. The results obtained showed that the electrochemical impedance electrode Ti/Pt(30%)RuO2 (35%)SnO2(35%) has a lower charge transfer resistance